Adherence to Traditionally Masculine Norms and Condom-Related Beliefs: Emphasis on African American and Hispanic Men. - Vincent, Wilson; Gordon, Derrick M; Campbell, Christina; Ward, Nadia L; Albritton, Tashuna; Kershaw, Trace (Psychology of men & masculinity, 2016)
Although studies have shown that adherence to traditional masculine norms (i.e., Status, Toughness, Antifemininity) affect men's attitudes toward sexual health, there is little research on how men's adherence to these norms affect them in the context of heterosexual, dyadic relationships. Among 296 young pregnant couples, we investigated the extent to which adherence to traditional masculine norms affected male and female partners' own condom-related beliefs (i.e., condom self-efficacy, positive condom attitudes) and that of their partners. We tested an interdependence model using a dyadic-analytic approach to path analysis. We also tested for differences across gender and race-ethnicity (i.e., African American, Hispanic). Results showed that adherence to the Antifemininity and Toughness masculine norms predicted negative condom-related beliefs, whereas, overall, adherence to the Status norm predicted positive condom-related beliefs. Men's and women's adherence to traditional norms about masculinity were associated with their partner's condom self-efficacy, and moderated associations based on gender and race-ethnicity were detected. In contrast, each dyad member's traditional masculine norms were not associated with his or her partner's positive condom attitudes. Taken together, findings indicated that the roles of traditional masculinity and condom-related beliefs in sexual health should be addressed within the context of relationships and associations between masculine norms and condom-related beliefs are not uniformly negative.